Conéctate : introductory Spanish / Grant Goodall, Darcy Lear - Goodall, GrantAuthor
Students of Introductory Spanish learn best when they are connecting - with authentic culture, with each other as a community, and with the language as used in real-world settings. This title gives students the opportunity to explore language and culture through interactive activities that keep them focused and engaged.